Radiofrequency ablation of atrial fibrillation—50 W or 90 W?. (8th October 2022) - Mueller, Julian; Nentwich, Karin; Ene, Elena; Berkovitz, Artur; Sonne, Kai; Chakarov, Ivaylo; Barth, Sebastian; Waechter, Christian; Behnes, Michael; Akin, Ibrahim; Halbfass, Philipp; Deneke, Thomas
Abstract: Background: This study sought to evaluate the short and midterm efficacy and safety of the novel very high power very short duration (vHPvSD) 90 W approach compared to HPSD 50 W for atrial fibrillation (AF) ablation as well as reconnection patterns of 90 W ablations. Methods and Results: Consecutive patients undergoing first AF ablation with vHPvSD (90 W; predefined ablation time of 3 s for posterior wall ablation and 4 s for anterior wall ablation) were compared to patients using HPSD (50 W; ablation index‐guided; AI 350 for posterior wall ablation, AI 450 for anterior wall ablation) retrospectively. A total of 84 patients (67.1 ± 9.8 years; 58% male; 47% paroxysmal AF) were included (42 with 90 W, 42 with 50 W) out of a propensity score‐matched cohort. 90 W ablations revealed shorter ablation times (10.5 ± 6.7 min vs. 17.4 ± 9.9 min; p  = .001). No major complication occurred. 90 W ablations revealed lower first pass PVI rates (40% vs. 62%; p  = .049) and higher AF recurrences during blanking period (38% vs. 12%; p  = .007). After 12 months, both ablation approaches revealed comparable midterm outcomes (62% vs. 70%; log‐rank p  = .452). In a multivariable Cox regression model, persistent AF (hazard ratio [HR]: 1.442, 95% confidence interval [CI]: 1.035–2.010, p  = .031) and increased procedural duration (HR: 1.011, 95% CI: 1.005–1.017, p  = .001) were identified as independent predictors of AF recurrence during follow‐up. Conclusions: AF ablation using 90 W vHPvSD reveals a similar safety profile compared to 50 W ablation with shorter ablation times. However, vHPvSD ablation was associated with lower rates of first‐pass isolations and increased AF recurrences during the blanking period. After 12 months, 90 W revealed comparable efficacy results to 50 W ablations in a nonrandomized, propensity‐matched comparison.